متطلبات تفعيل التسويق الإلكتروني لخدمات التأمين في الجزائر 2010-2022 - بودرومي عبد العزيز (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
الملخص هدف الباحث من خلال دراسة موضوع متطلبات تفعيل التسويق الإلكتروني لخدمات التأمين في الجزائر ،2022-2010إلى تسليط الضوء على أهمية الدور المحوري الذي يمكن ان يلعبه التسويق الإلكتروني في تطوير الخدمة التأمينية وضمان استمرارية المؤسسات التأمينية والرفع من قدراتها التنافسية، من خلال تبين العلاقة بين تفعيل متطلبات التسويق الإلكتروني وتطوير خدمات التأمين في الجزائر، حيث اعتمد على فرضية رئيسية لاختبار العلاقة الموجودة بين المتغير المستقل ( متطلبات تفعيل التسويق الإلكتروني) والمتغير التابع ( الخدمة التأمينية)، وذلك من خلال اعداد استبيان مصمم وفق مقياس ليكارت الخماسي وتوزيعه كأداة لجمع البيانات الأولية المتعلقة بموضوع الدراسة، وقسم الى محورين وتضمن المحور الأول على متطلبات تفعيل التسويق الإلكتروني ويشمل 41عبارة، أما المحور الثاني فقد اشتمل على مؤشرات الخدمة التأمينية ويضم 26عبارة، وقد شملت هذه الدراسة استطلاع آراء عينة غير عشوائية من موظفي القسم التجاري لمؤسسات التأمين الناشطة في السوق الج ازئري ( 23مؤسسة مركزية بالإضافة الى الوكالات الجهوية المنتشرة في ارجاء الوطن)، وتم استرداد 50اجابة، كما اعتمد الباحث على برنامج التحليل والمعالجة الإحصائية SPSSفي تحليل المعلومات والبيانات المسترجعة ومعالجتها، وقد خلصت الدراسة الى مجموعة من النتائج أهمها: ضعف تطبيق التسويق الإلكتروني في مؤسسات التأمين الجزائرية، بالرغم من وجود علاقة ارتباط بين متطلبات تفعيل التسويق الإلكتروني والخدمة التامنيية، ويرجع ذلك الى عدة اعتبارات أهمها قصور التنظيم القانوني وضعف البنية التحتية ، وضعف الثقافة التأمينة لدى الفرد في الجزائر، الا ان التغيرات التكنولوجية المتسارعة جعلت من الخدمة التأمينية الإلكترونية امرا حتميا في تطوير قطاع التأمين. الكلمات المفتاحية: التسويق الإلكتروني، الخدمة التأمينة، التأمين، التسويق الإلكتروني لخدمات التأمين، المزيج التسويقي، متطلبات تفعيل التسويق الإلكترونيAbstract: The aim of the researcher in studying the topic "Requirements for Activating E-Marketing for Insurance Services in Algeria 2010-2022" is to highlight the crucial role that e-marketing can play in developing insurance services, ensuring the sustainability of insurance institutions, and enhancing their competitive capabilities. This is achieved by examining the relationship between activating the requirements for e-marketing and developing insurance services in Algeria. The researcher relied on a main hypothesis to test the relationship between the independent variable (requirements for activating emarketing) and the dependent variable (insurance services). A questionnaire designed according to the five-point Likert scale was prepared and distributed as a tool for collecting primary data related to the study topic. It was divided into two sections: the first section covered the requirements for activating emarketing and included 41 items, while the second section included indicators of insurance services comprising 26 items. This study surveyed the opinions of a non-random sample of employees from the commercial departments of insurance institutions active in the Algerian market (23 central institutions in addition to regional agencies spread across the country), and 50 responses were retrieved. The researcher also relied on the SPSS program for statistical analysis and processing of the retrieved data. The study concluded with a set of findings, the most important of which is the weak implementation of e-marketing in Algerian insurance institutions, despite the existence of a correlation between the requirements for activating e-marketing and insurance services. This is attributed to several factors, the most significant being the inadequacy of legal regulations, weak infrastructure, and a lack of insurance culture among individuals in Algeria. However, the rapid technological changes have made electronic insurance services an inevitable necessity for developing the insurance sector. Keywords: Electronic Marketing, Insurance Service, Insurance, Electronic Marketing for Insurance Services, Marketing Mix, Electronic Marketing Activation Requirements
Keywords: الخدمة التأمنية; التأمين; خدمات التأمين; متطلبات التفعيل; خدمات التأمين في الجزائر